Trial of Optimal Personalised Care After Treatment—Gynaecological Cancer (TOPCAT-G): A Randomized Feasibility Trial. Issue 2 (1st February 2018) - Morrison, Val; Spencer, Llinos H.; Totton, Nikki; Pye, Kirstie; Yeo, Seow Tien; Butterworth, Caryl; Hall, Liz; Whitaker, Rhiannon; Edwards, Rhiannon Tudor; Timmis, Laura J.; Hoare, Zoe; Neal, Richard D.; et al.
Abstract : Objective: This study aimed to evaluate the feasibility of completing a parallel-group randomized controlled trial to compare usual follow-up care for women who have completed treatment of gynecological cancer against a nurse-led telephone intervention, known as Optimal Personalised Care After Treatment—Gynaecological. Methods: The unblinded trial aimed to recruit patients who had completed treatment of cervical, endometrial, epithelial ovarian, or vulval cancer within the previous 3 months at 3 North Wales hospitals. We randomized participants to either usual hospital-based follow-up or specialist nurse–led telephone education, empowerment, and structured needs assessment follow-up. The primary outcomes assessed the feasibility of running a larger trial including patient eligibility, recruitment and retention rates, and outcome measure completion. Secondary outcomes were generic and health-related quality of life and a patient self-report health service use (Client Service Receipt Inventory) data collected at 3 time points (baseline, 3 months, and 6 months). Results: Of the 58 women screened, 44 were eligible (76%) and 24 (55%) were recruited and randomized (12:12 to control and intervention, respectively). One participant was lost to follow-up. Recruited participants had a mean (SD) age of 60 (11.2) years and were approximately 5 months from their initial diagnosis (mean [SD], 159 [58] days). Seventeen (71%) of the participants had an endometrial cancer diagnosis. All outcome measure completion rates exceeded 96%. Although not a core feasibility objective, analyses of outcome measures indicated positive changes in quality of life and well-being within the Optimal Personalised Care After Treatment—Gynaecological group; exploratory cost consequence analysis indicated that the nurse-led intervention had a mean total service use cost of £27 per patient (bootstrapped 95% confidence interval, −£290 to £240) lower than did the standard care group. Conclusion: Eligibility, recruitment, and retention rates as well as outcome measure completion showed that the trial is feasible.